Acceleration Analysis of Bank SulutGo Lolak Branch Office Development Project Time - Deyke J. F. Mandang; Estrellita V. Y. Waney; Sherley Runtunuwu; Don Kabo (Jurnal Multidisiplin Madani, 2024)
Project success is usually measured by short success time and minimal cost without ignoring the quality of the results. Construction project delays, namely procurement of materials that are not on schedule, labor performance that does not follow the current progress of the work, weather factors are also included in the delay in the implementation of work and the cause of delays in the project, one of which is the failure in the construction of the fence resulting in the collapse of the fence and the repetition of the work. The crash program method is one way that can be used to optimize time and cost in a project. This discussion uses time acceleration and the addition of overtime hours. means accelerating work that is on the critical path, each acceleration carried out will be evaluated based on the cost and how long the project can be accelerated in this way. The calculation results use time acceleration with the addition of overtime hours with the alternative used is the addition of working hours (overtime). The time of the project acceleration is 204 HK with a total project cost of Rp. 8,554,773,321.64, while the completion of normal time is 245 HK with a total project cost of Rp. 8,582,694,112.09. The acceleration result is a reduction in time of 41 HK with an additional total project cost of Rp. 27,920,790.45